Trabalho e educação profissionalizante do centro vocacional tecnológico (CVT) na comunidade de Umarizeiras, Maranguape-CE - Maciel, Paulo Henrique Freitas (2013)
Historically, we can verify the educational duality in which we have a formation oriented to the ruling élite and another one oriented to the workers who act in the capitalist production process. However, the expansion of the capitalism in the last four decades, we identify, as Karl Marx had already previewed, the intensification of the substitution of the living work (the human being) for the dead work (machines), causing crisis, because the market doesn’t absorb so many workers in the production process. Therefore, the unemployment, is a reality that scares even the international organizations, like the United Nations (UN). In this context, the employability, in a world without jobs and the human capital theory emerge as new forms of social domination, internalizing in the individual the idea that he is the responsible for his precarious economic situation. In this regard, in this research we analyzed the formation of workers released by Centro Vocacional Tecnológico (CVT) – Technologic Vocational Center – through means of initial formation courses or professional qualification in the community of Umarizeiras, in Maranguape, town in the Metropolitan Region of Fortaleza, pointing contradictions imposed by the contemporary capitalism which limit that performance. The investigation took place with oral sources, through interviews with thirteen dwellers; and documents: booklets of the courses available by CVT and Estatuto da Associação de Moradores de Umazeira, which let us highlight the contradictions between the official speech and the reality lived by the subjects involved in that formation. The available courses by CVT to that community were fruit pulp process, chicken raising, E.V.A., computing, fruit sweets. All the interviewed subjects had already participated in one or more courses, motivated by the immediate objective of getting a job, fact that doesn´t really happen; about the knowledge acquired in the courses, it’s rare to find someone who uses it in the daily life. We conclude, therefore, that the offer of the courses achieves rather an ideological objective, targeting to blame the individuals for their economic situation than a whole formation of the human being, having work as the educational principle.